2017
DOI: 10.1002/2211-5463.12184
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit‐induced oxidative stress affects artemisinin content and expression of proline metabolic genes in Artemisia annua L.

Abstract: Water stress is one of the most critical abiotic stresses that restricts growth, development, and alters physiological and biochemical mechanisms of plant. The effects of long‐term water shortage‐induced oxidative stress on morphophysiological parameters, proline metabolic genes, and artemisinin content were studied in Artemisia annua L. under greenhouse conditions. Plant growth, biomass accumulation, relative water content, and chlorophyll content were reduced under drought. Leaf water potential ranged from −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Water stress enhanced the activity of DHAR in the pepper seedlings. Similar results have already been reported in Agropyron cristatum (Shan and Liang 2010) and Artemisia annua (Soni and Abdin 2017) under WS. The application of SA caused further elevation in DHAR activity in mustard (Alam et al 2013) as is also seen in this study.…”
Section: Nr Mediates No Synthesis In Sa-reversed Oxidative Stress Under Wssupporting
confidence: 90%
“…Water stress enhanced the activity of DHAR in the pepper seedlings. Similar results have already been reported in Agropyron cristatum (Shan and Liang 2010) and Artemisia annua (Soni and Abdin 2017) under WS. The application of SA caused further elevation in DHAR activity in mustard (Alam et al 2013) as is also seen in this study.…”
Section: Nr Mediates No Synthesis In Sa-reversed Oxidative Stress Under Wssupporting
confidence: 90%
“…The P5CS1 expression was reported to be highly activated, while PDH isoforms were moderately stimulated during drought conditions resulting in increased proline levels in the tobacco plants [29]. Another study demonstrated significantly induced levels of the major proline biosynthesis genes, including P5CS1 and PDH1 in Artemisia plants subjected to drought stress [30]. Similar findings were recorded in our study, where the melatonin applied appeared to impede the drastic stimulation of the PDH1 and P5CS1 expressions in the MPEG plants compared to that of the PEG plants ( Figure 2C,D).…”
Section: Discussionmentioning
confidence: 97%
“…Proline plays multiple roles in higher plants, including maintenance of membrane integrity, removal of ROS, regulation of osmotic pressure, and acting as an osmoprotectant against a range of abiotic stresses, including high salinity [33]. An increase in the endogenous proline content is known to confer abiotic stress tolerance and is associated with upregulation of the P5CS1 gene and downregulation of the PDH gene [34,35]. P5CS1 is involved in the first step of proline synthesis and catalyzes the conversion of L-glutamic acid to glutamate-5-semialdehyde [33].…”
Section: Discussionmentioning
confidence: 99%